Analisis butir soal tes literasi matematika dan efikasi diri peserta didik - Eka Mega Nanda; Kismiantini Kismiantini; Elly Arliani (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the quality of daily test items and non-test instruments (questionnaires) on Two-Variable Linear Equation Systems in junior high school, in terms of validity, reliability, discrimination power, and difficulty level. The method used was descriptive analysis with 64 eighth-grade students (academic year 2024/2025) as subjects. The findings show that all instruments are valid (essays are very high, multiple-choice questions and questionnaires are high), but the reliability of exam questions (essays and multiple-choice questions) is still in the moderate category. Further analysis of multiple-choice questions shows a predominance of easy difficulty levels (92%) and a number of items (25%) with poor discrimination power, indicating the need for item revision.